PERSEPSI KONSUMEN KREDIT USAHA RAKYAT (KUR) TERHADAP PELAYANAN PT BANK RAKYAT INDONESIA Tbk. UNIT LANGOWAN - Frendi H. Wurarah; Grace A.J. Rumagit; Joachim N.K. Dumais (COCOS, 2016)
ABSTRACTConsumer perception or perspective with the services provided by the bank is the rating of the consumers to the services of the bank. The bank also should understand what consumers think and feel about the services provided, whether it gives satisfaction to the consumer or not. In connection with the BRI bank's vision that is becoming a leading commercial bank that always put customer satisfaction, and one of the mission is to provide excellent service to customers through a widespread network supported byprofessional human resources. That is why the authors are interested in carrying out research on consumer perceptions of people business credit (KUR) to service on Bank BRI LangowanUnit. The objektive of this research to analyze the perception of consumer credit (KUR) to service at the Bank Rakyat Indonesia (BRI) Langowan Unit, based on the variables to be studied, namely, Tangibles, Reliability,Responsiveness, Assurance,Empathy, using a Likert Scale analysis tools. This aims was conducted over four months from February to the month of May 2016 from preparation to the arrangement of research reports. The Location of research is Bank Rakyat Indonesia LangowanUnit. This study uses primary data and secondary data. Primary data were obtained from 73 respondents from credit consumers use the questionnaire. While secondary data obtained from the Bank BRI. The sampling method in this study usespurposive sampling. The results of this research showed that the perception of consumer credit (KUR) to service at the BRI Langowanunit was relatively satisfied with regard to the five variables studied namely Tangible, Reliability, Responsiveness, Assurance, and Empathy.Key Word: Perception, Consumer, Business Credit (KUR), PT Bank Rakyat Indonesia